Introduced European bison (Bison bonasus) in a confined forest district: A ten year parasitological survey - K. Buchmann; L.-L. Christiansen; P.W. Kania; S.M. Thamsborg (International Journal for Parasitology: Parasites and Wildlife, 2022)
In the year 2012 a total of seven individuals (one bull and six cows) of European bison (Bison bonasus) were introduced to a fenced 200 ha area in a forest district (Almindingen, Island Bornholm, Denmark) in the Baltic Sea. In 2017 the herd was supplemented by introduction of another bull. The animals all originated from a population in the Polish Bialowieza forest. Faecal samples were recovered with intervals and subjected to a copro-parasitological investigation (applying egg flotation, sedimentation and Baermann technique). In addition, parasites were sampled during necropsy of animals euthanized or found dead three years after introduction. The animals carried a range of parasite types including trematodes (liver fluke Fasciola and rumen fluke), cestodes (Moniezia), nematodes (Dictyocaulus viviparus, trichurids, and other gastrointestinal nematodes (GIN) including Trichostrongylus axei and Haemonchus contortus). Egg and larval morphology also suggested presence of GIN genera Nematodirus, Ostertagia and Cooperia. The trematodes did not establish a life cycle in the recipient area, as judged by examination of calves born in the new area, but the cestode and several nematode species occurred in these animals. Especially Dictyocaulus viviparus was successfully spread and occurred together with GIN at moderate to high infection intensities at most sampling points. The reproduction among bison in the herd was high during the first few years. The exact birth rate is unknown but up to 24 calves are believed to be born during the ten year study period. Mortality among adults and calves occurred and in early June 2022 the total number of live animals was 11 (seven males, three females, one calf). The possible impact of the parasite infections on the bison health and future wildlife infection status is discussed.